Peningkatan Identitas Melalui Plng Jalang: Studi Kasus Program KKN Tematik Di RT 23 Sawah Lebar - Latifah, Diana; Wirayuda, Sahrul; Efendi, Irpan; Puspita, Lidya; Sianturi, Erwin Halomoan; Fadilla, Rohayu; Kanedi, Indra; Putra, Dhanu Ario (Jurnal Kewirausahaan & Inovasi, 2026)
The lack of street signs in RT 2 3 SawahLebar makes it difficult for residents and visitors to find locations and weakens the area’s identity. This community service program aims to strengthen local identity through street sign installation. This research used a qualitative case study method with observation, interviews, and documentation. The results show that the signs improved navigation, strengthened residents’ sense of belonging, and enhanced the area’s organized image. Challenges included limited funding and incomplete street name data. This program proves that simple street signs can support local identity if planned and maintained collectively.